Pharmacoepidemiology of Drugs Used in Indoor Patients of Orthopaedic Department at a Tertiary Care Hospital - Minal Jain; Rajesh S Hiray (Research Center for Rational Use of Drugs (RCRUD), 2024)
Background: Globally, with the increasing orthopaedic admissions, the management modalities have also been evolving. With the focus mainly on reducing hospital stay and improving quality of life, pharmacotherapy is a keystone in management. Thus, the present study was undertaken to assess the drug utilization in orthopaedic inpatients. Methods: This is a cross sectional, observational study. Data was collected from prescriptions of 200 patients admitted in the Orthopaedic ward and evaluated for WHO Drug Use Indicators and potential drug-drug interactions (pDDI) and prescription pattern was noted. Adverse Drug Reactions (ADR) were noted and assessed. Results: A total of 2046 drugs were prescribed in 200 prescriptions. Average number of drugs per prescription is 10.23. Antimicrobials (25.76%) was the most common class of drug prescribed followed by supplements (20.28%) and analgesics (16.13%). 79.42% drugs were prescribed by generic name, 82.06% were from the NLEM and 99.9% drugs were from hospital pharmacy. Antibiotics prescribed were as per WHO AWaRe guidelines. ADR noted in 4 patients with drug being discontinued in one case. pDDI were seen in 98% prescriptions with 95.8% being Pharmacokinetic interactions. Conclusion: Current study provides insight into the drug utilisation pattern, highlighting the extensive use of antibiotics and analgesics in orthopaedic inpatients. Adherence to WHO guidelines helps reduce antibiotic resistance and promotes better patient care.